Overcoming Judicial Innumeracy: A Proposal to Bring the Venerable Process of Peer Review to the Enduring Problem of Courts’ Scientific Illiteracy - Faigman, David (Science and Technology Law Review, 2025)
Lawyers are not known for their proficiency in math and science. Most of us who went to law school reached a point in our math and science studies when we realized that neither medicine nor engineering were likely to be successful career paths. It is these lawyers who become judges. Yet, the United States Supreme Court has increasingly put the burden for deciding complex scientific and technical questions in the hands of judges. This Article explores this trend of putting greater responsibility for deciding scientific and technical issues on judges, particularly in the areas of evidence law, administrative law, and constitutional law. I do not, however, uniformly decry this trend. In many contexts, both as a matter of legal doctrine and as an empirical matter, judges are the appropriate decision makers for scientific and technical questions. The problem is that they, on the whole, are so unqualified for this task. The question, then, is how courts might be better prepared to make informed decisions about scientific and technical questions. I propose a solution that comes from the scientific enterprise itself, peer review. While not a perfect solution, peer review has proved to be the best available option for evaluating the validity and value of scientific research. I explore how a formal procedure of peer review might be employed by courts to provide them with independent assessments of expert reports.